The Effect Of Puzzle Games On Reducing Impulsive Behavior In Hyperactive Children Aged 5-6 Years - Sri Puspita Wulandari Paputungan; Ardini, Pupung Puspa; Sutisna, Icam (Program Studi Magister Pendidikan Anak Usia Dini, 2025)
The study problems are: